Designing Website as Digital Marketing to Promote Construction Company (A Case Study of PT NLA) - Nabila Syachfitria; Annisa Rahmani Qastharin (Mandalika Journal of Business and Management Studies, 2024)
In this era of globalization, the construction industry continues to grow and significantly contributes to economic growth in Indonesia. However, the industry faces intense business competition and market dynamics that continue to change every year. These conditions pose challenges for companies to continuously develop and adjust their business strategies. One viable business strategy is the use of digital marketing as a promotional tool to reach a wider target audience, enhance the company's positive image, and increase brand awareness. Digital marketing can be implemented by companies through the use of websites to build the company's online presence. A website aims to improve the company's visibility and serve as accessible information for all people. In this context, PT NLA is a construction company in West Java that needs to implement a website as a digital promotional tool. Currently, the company does not have a website to introduce and market its services. As a result, PT NLA has limited information available on various online platforms due to the absence of direct information from an official company website. Therefore, having a company website is crucial for long-term marketing investment. This research aims to analyze and design two prototype website concepts to provide recommendations for the company. The research employs the design thinking method to assist in the analysis and design of the website prototypes for PT NLA. It also uses a mixed-methods approach to enrich the data. Qualitative data will be collected through semi-structured interviews with internal and external company stakeholders, while quantitative data will be used during the testing phase in the form of the System Usability Scale (SUS). The testing phase aims to obtain evaluation scores and feedback from both internal and external company stakeholders regarding the two prototypes designed by the researchers. These prototypes will be tested and evaluated based on the highest scores and validation from the company's internal stakeholders. The research results indicate that the second prototype website concept received the highest scores compared to the first prototype. This concludes that the second prototype is the best website concept that can be implemented by the company.